2002
DOI: 10.1037/0022-3514.83.5.1029
|View full text |Cite
|
Sign up to set email alerts
|

Putting the brakes on prejudice: On the development and operation of cues for control.

Abstract: A model concerning the establishment and operation of cues for control was developed and tested to understand how control can be exerted over (automatic) prejudiced responses. Cues for control are stimuli that are associated with prejudiced responses and the aversive consequences of those responses (e.g., guilt). In Experiments 1 and 2, 3 events critical to the establishment of cues occurred: behavioral inhibition, the experience of guilt, and retrospective reflection. In Experiment 3, the presentation of alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
297
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(315 citation statements)
references
References 68 publications
15
297
2
1
Order By: Relevance
“…These results appear to be in line with the assertion that when an individual recognizes the difference between their perceived behavior and the way they actually behave they may undergo a global feeling of discomfort, which leads to the individual engaging in efforts to decrease this discrepancy (Festinger, 1957;Monteith, Ashburn-Nardo, Voils, & Czopp, 2002). As such, in combination with ISC, simply making an individual consciously aware of their implicit attitudes may act as a 'cue for control' − increasing self-regulatory behavior and reducing stereotypical attitudes (ibid).…”
Section: Discussionsupporting
confidence: 76%
“…These results appear to be in line with the assertion that when an individual recognizes the difference between their perceived behavior and the way they actually behave they may undergo a global feeling of discomfort, which leads to the individual engaging in efforts to decrease this discrepancy (Festinger, 1957;Monteith, Ashburn-Nardo, Voils, & Czopp, 2002). As such, in combination with ISC, simply making an individual consciously aware of their implicit attitudes may act as a 'cue for control' − increasing self-regulatory behavior and reducing stereotypical attitudes (ibid).…”
Section: Discussionsupporting
confidence: 76%
“…Analysis using the Quad model showed that the negation training not only weakened participants' automatically activated associations (AC) but also improved their ability to determine the correct response (D). Th e fi nding of enhanced detection is consistent with the idea that training enables individuals to develop cues for recognizing and then controlling non-prejudiced responses (Monteith et al, 2002). Th is suggests that people can be trained to engage self-control in a manner similar to individuals who are internally motivated to be non-prejudiced (and, presumably, train themselves).…”
Section: Individual Differences In Motivation To Respond Without Prejsupporting
confidence: 65%
“…Analysis with the Quad model showed that the negation training not only weakened participants' automatically activated associations (AC) but also improved their ability to determine the correct response (D). According to Monteith and her colleagues (Monteith, Ashburn-Nardo, Voils, & Czopp, 2002), behavioral monitoring is an essential skill in responding without bias because successfully discriminating appropriate actions from inappropriate actions is a necessary precondition for regulating behavior. Our modeling results show that one of the benefits of antibias training is an increased ability to monitor appropriate behavior.…”
Section: Training To Negate Biased Associationsmentioning
confidence: 99%